Bacterial Fatty Acid Synthesis: Effect of Tween 80 on Antibiotic Potency Against Streptococcus Agalactiae and Methicillin-Resistant Staphylococcus Aureus - Krsta, Dragan; Ku, Caron; Crosby, Ian T.; Capuano, Ben; Manallack, David T. (Anti-Infective Agents, 2014)
The effect of varying concentrations of Tween 80 on the antimicrobial potency of platensimycin and triclosan was investigated using both Streptococcus agalactiae (S. agalactiae) and methicillin-resistant Staphylococcus aureus (MRSA). In the presence of very low concentrations of Tween 80 (0.02%) both platensimycin and triclosan were rendered ineffective against S. agalactiae. A linear concentration-dependence was found with the antimicrobial activity of triclosan against MRSA showing a loss in effectiveness with increasing concentrations of Tween 80. Platensimycin, on the other hand, demonstrated improved antibiotic activity at higher concentrations of Tween 80. The differential effects of these two agents have implications for the regulation of lipids in Gram positive organisms and the viability of bacterial fatty acid synthesis inhibitors as antibiotics.
Keywords: Tween 80